The Birthing of Things: Bergson as a Reader of Lucretius - Patrick Healy (Footprint)
I examine, in this short paper, the work of Henri Bergson on Lucretius first published in 1884, and argue for its vital significance in understanding the development of his philosophical thinking. This publication was to serve as an introduction to extracts from Lucretius, for his students at Clermont-Ferrand, with a commentary and notes on the poetry, philosophy, the physics, language and text of his poem De Rerum Natura. In the published volume most of the overview of Lucretius by Bergson is given in the long preface, and this is followed by extracts in Latin, without translation into French, with comments on lines and individual words, which covers all the books of the original poem. By 1899 it had gone to a third edition, and was still in print until the 1960's. Copies today are very difficult to obtain, and only recently has a full electronic version become available on the Internet Archive, to which readers are here directly referred.